Between Past and Future - 1/22
Contains the second part of Prof. Bartlomiej Kaminski’s speech in the last panel of the “Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" international conference held at CEU in March 1999. Bartlomiej Kaminski’s speech is followed by a presentations belonging to the Croatian historian and politician Ivo Banac and Prof. Ilya Prizel from John Hopkins University. Chairman of the panel is Alfred Rieber.